The Escalation of the Iran-US Conflict and Saudi Arabia's Response A Political Security Analysis of Middle East Stability - Muhammad Hizam, Ammar (Visi Pencerah Nusantara, 2026)
This study examines the escalation of the conflict between Iran and the United States. It analyzes Saudi Arabia's strategic response within the broader framework of regional political security and stability in the Middle East. Although previous studies have discussed the Iran–Saudi rivalry and the geopolitical tensions between Iran and the United States, most analyses remain fragmented and address these issues separately within the frameworks of foreign policy or specific regional conflicts. Consequently, limited research has comprehensively examined how the escalation of the Iran-US conflict interacts with Saudi Arabia’s strategic response and how this interaction influences regional security dynamics. This study employs a qualitative research design using the Systematic Literature Review (SLR) approach to identify, evaluate, and synthesize relevant scholarly works. Data were collected from the Dimensions Database and Scopus Database, focusing on peer-reviewed publications from 2021 to 2026 that specifically discuss the escalation of the Iran-US conflict and Saudi Arabia’s geopolitical strategies. The findings indicate that the Iran-US confrontation represents a multidimensional geopolitical rivalry shaping regional security structures, alliance formations, and proxy conflicts across the Middle East. In response, Saudi Arabia adopts adaptive strategies through a combination of balancing and hedging, reflected in regional security cooperation, diplomatic engagement, and domestic policy adjustments. However, the intensification of geopolitical rivalry also contributes to structural instability, political polarization, and increasing regional uncertainty, suggesting that sustainable Middle Eastern stability depends on the capacity of regional and global actors to manage strategic competition and develop inclusive collective security mechanisms.